Religious Songs on Youtube: The Impact on Students - Supriyadi, Tedi; Julia, Julia (Mimbar Sekolah Dasar, 2018)
Beginning in 2018 Indonesian people are treated to religious songs from Sabyan Gambus group whose vocalist Nissa Sabyan. The songs sung by Nissa Sabyan echoed almost in every layer of the society. One of the media that made it easy for people  to enjoy various songs from several Nissa Sabyan albums is YouTube. This paper was aimed to analyze the YouTube's role of students' religious dimension. The method used in this research is a survey with a qualitative approach. The survey was conducted on 147 students. The results of the study prove that YouTube as an Internet-based audio-visual media is an effective medium for spreading religious nuances. The majority of students feel to be religious by listening to Nissa Sabyan's songs, even though they don't understand the contents of the lyrics. Thus, it can be concluded that YouTube has a significant  role in fostering a religious sense of students.